DNA Damage and Repair Deficiency in ALS/FTD-Associated Neurodegeneration: From Molecular Mechanisms to Therapeutic Implication - Wang, Haibo; Kodavati, Manohar; Britz, Gavin W.; Hegde, Muralidhar L. (Frontiers in Molecular Neuroscience, 2021)
Emerging studies reveal that neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), are commonly linked to DNA damage accumulation and repair deficiency. Neurons are particularly vulnerable to DNA damage due to their high metabolic activity, relying primarily on oxidative phosphorylation, which leads to increased reactive oxygen species (ROS) generation and subsequent DNA damage. Efficient and timely repair of such damage is critical for guarding the integrity of genomic DNA and for cell survival. However, notably, several genes expressing RNA/DNA binding proteins (RBPs) and associated cellular processes implicated in ALS have also been linked to FTD, suggesting that the two diseases share a common underlying pathology with varied clinical manifestations. A key question in the etiology of the ALS/FTD spectrum of neurodegeneration is the mechanisms and pathways involved in genome instability caused by diverse RBP gene mutations. The understanding of such converging molecular mechanisms provides insights into the underlying etiology of the rapidly progressing neurodegeneration in ALS/FTD, while also revealing novel DNA repair target avenues for therapeutic development. In this review, we summarize the common mechanisms of neurodegeneration in ALS and FTD, with a particular emphasis on the DNA repair defects induced by ALS/FTD causative genes. We also highlight the consequences of DNA repair defects in ALS/FTD and the therapeutic potential of DNA damage repair-targeted amelioration of neurodegeneration.